Computational fluid dynamics simulation of jet in crossflow - Ahmad Anwar (2014)
Jet in crossflow, also known as transverse jet, refers to a jet of fluid which exits an orifice into a primary fluid that flows across the orifice. The jet is eventually deflected into the crossflow by bending into the stream wise direction. Currently, the grey water system which discharges waste water out of the commercial Airbus aircraft via the drain mast produces long streaks of reddish-brown stains on the aircraft belly. The purpose of this project is to study the effects of modifying the drain mast of Airbus A330-300 commercial aircrafts, to reduce the amount of reddish-brown stains. The initial stage of the project involved using Computational Fluid Dynamics simulations to validate jet in crossflow experiments, from a reference case titled “Mixing, structure and scaling of the jet in crossflow” by S.H. Smith and M.G. Mungal (1998). Steady state 2D simulations were performed using the realizable k-epsilon turbulence model was used, followed by 3D simulations in both the steady and transient state. The steady state 3D simulations used realizable k-epsilon model while the transient simulations used Large Eddy Simulations (LES). Results showed that LES simulations proved to be generally more accurate. An error value of 0.459% was achieved for the LES simulation case with velocity ratio of 15, compared to 32.5% for the corresponding k-epsilon case. However, the realizable k-epsilon turbulence model was chosen for the subsequent simulations of jet from the drain mast in crossflow, due to the less computational costs involved. The final simulations of jet from the drain mast studied the effects of varying the height of the drain mast and also the jet exit diameter as part of a 2k experiment. The cruise flight conditions at 11,000m altitude and 0.86 Mach were chosen as boundary conditions. It can be concluded that a higher drain mast height and smaller jet exit diameter would produce the least amount of stains on the aircraft belly. The configuration with the greater height of 60 mm and jet exit diameter of 2.5 mm produced the least amount of acetone mass on the ground of the test domain at a value of 7.451x10-6. This project could be extended by including more extensive data such as the actual geometry of the drain mast, real time flight conditions, and actual aerodynamic flow data at the belly region of the aircraft.